The Receptor-Like Cytoplasmic Kinase STRK1 Phosphorylates and Activates CatC, Thereby Regulating H2O2 Homeostasis and Improving Salt Tolerance in Rice - Zhou, Yan-Biao; Liu, Cong; Tang, Dong-Ying; Yan, Lu; Wang, Dan; Yang, Yuan-Zhu; Gui, Jin-Shan; Zhao, Xiao-Ying; Li, Lai-Geng; Tang, Xiao-Dan; Yu, Feng; Li, Jiang-Lin; et al. (The Plant cell, 2018)
Salt stress can significantly affect plant growth and agricultural productivity. Receptor-like kinases (RLKs) are believed to play essential roles in plant growth, development, and responses to abiotic stresses. Here, we identify a receptor-like cytoplasmic kinase, salt tolerance receptor-like cytoplasmic kinase 1 (STRK1), from rice (Oryza sativa) that positively regulates salt and oxidative stress tolerance. Our results show that STRK1 anchors and interacts with CatC at the plasma membrane via palmitoylation. CatC is phosphorylated mainly at Tyr-210 and is activated by STRK1. The phosphorylation mimic form CatCY210D exhibits higher catalase activity both in vitro and in planta, and salt stress enhances STRK1-mediated tyrosine phosphorylation on CatC. Compared with wild-type plants, STRK1-overexpressing plants exhibited higher catalase activity and lower accumulation of H2O2 as well as higher tolerance to salt and oxidative stress. Our findings demonstrate that STRK1 improves salt and oxidative tolerance by phosphorylating and activating CatC and thereby regulating H2O2 homeostasis. Moreover, overexpression of STRK1 in rice not only improved growth at the seedling stage but also markedly limited the grain yield loss under salt stress conditions. Together, these results offer an opportunity to improve rice grain yield under salt stress.